Pemanfaatan Buah Mangrove Sebagai Sumber Makanan Alternatif di Halmahera Barat, Maluku Utara - Jailan Sahil; Irham Soamole (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2013)
This study aims to determine: (1) how the management of mangrove fruit as alternative food ingredients (2) types of mangrove that use by people as alternative food items. The method used in this research is the development of research that displayed products to be produced and can be implemented. The results showed that the process of making mangrove fruit as food begins with boiling mangrove fruit, stripping, immersion with ash, drying and milling into flour. Furthermore, the starch is used as raw material for making dry or wet cake. The organoleptic test used to determine the level of preference or the viability of a product to be accepted by the panelists (consumers) includes flavor, aroma, texture and color. The 30 respondents answered 4 (preferred) and 5 (strongly preferred). This shows that they like the products from these two types of mangrove.Keywords: alternative food, mangrove fruit, North Maluku